Bolsonarismo e a manipulação do brasileiro autoritário: nazifascismo a serviço do neoliberalismo - Monteiro, Edson Lopes da Silva (2023)
This study aims to verify whether former President Jair Bolsonaro, the Bolsonarist movement or simply Bolsonarism, the Bolsonarist communication and Bolsonaro’s government, exercised from 2019 to 2022, are, according to Max Weber – the theoretical framework of this research – ideal types or typical phenomena of Nazi-facist leader, movement, communication and government. In the first chapter, based on the historical accounts of Robert Paxton, Roderick Stackelberg, Eric Hobsbawn and Nicos Poulantzas, as well as on the inducing concepts of fascism by Umberto Eco and Michael Mann, it is possible to sustain by deduction, that Bolsonarism is an ideal typical phenomenon of Nazi-fascist movement and that Bolsonaro’s government followed a Nazi-fascist orientation. Despite of the fact that it was not implemented a Nazi-fascist regime in Brazil, democracy was demeaned in order to comply with neoliberalism, with which Bolsonarism and neo-Pentecostalism have broad elective affinities – another Max Weber’s concept. The second chapter analyzes the discourse and the strategy of communication of Jair Bolsonaro, Bolsonarism and other current farright leaders and populist movements in Europe and the United States, to find that they follow patterns inaugurated a century ago by Nazi-fascism, what is affirmed considering the mirroring between communicational practices of the original European Nazi-fascism and the fascist communication in the post-war USA, according to research and analysis by Theodor Adorno in this period, as well as the discourse and communication techniques of the current populist extreme right in Europe and America. Beside stating that Jair Bolsonaro is an ideal type of Nazi-fascist leader and that Bolsonarist communiciation is a typical phenomenon of Nazi-fascist communication, in the third chapter, based on the concepts of authoritarian personality or potential fascist, formulated by Theodor Adorno in the 1940s, it is also demonstrated, through quantitative and, mainly, qualitative empirical research, that the Bolsonarist radicalized supporter is an ideal type of authoritarian personality, a potentially Nazi-fascist individual